PENGARUH MODEL COOPERATIF LEARNING TIPE JIGSAW TERHADAP HASIL BELAJAR MATA KULIAH PENANGANAN KEGAWATDARURATAN PADA MAHASISWA SEMESTER V - Ika Mardiyanti (Universitas Nahdlatul Ulama Surabaya, 2018)
The learning model is one of the factors that influence student results. This study aims to determine the effect of cooperative learning model Jigsaw mode on the Result of Learning Emergency Management Course in Student Semester V at the University of NU Surabaya in 2015. The design of this research was Quasi Experimental cross sectional approach. The population in this study were all students throughout the class A fifth semester at the University of Nahdlatul Ulama Surabaya in 2015 amounted to 44 people. Samples were taken by sampling saturated, which in the 4 groups: the experimental group consisted of prior Jigsaw, after Jigsaw and the control group consisted of before the lecture, lecture sesuadah. The dependent variable in this study is the Learning Outcomes Management Training Courses Emergency Resuscitation On the newborn infant, and the independent variable is the type cooperative learning model Jigsaw. The research instrument used questionnaires, the data were analyzed by Friedman test with significance level α = 0.05. Research shows that student results after using cooperative learning model Jigsaw mode almost half (33.3%) get an A, while after using lecture learning model minority (23.8%) of respondents received an A. From the analysis of Friedman Test level significance α = 0.05, p = 0.000 thus obtained H0 rejected because p <α which means there Effect Model Jigsaw cooperative learning mode Learning Results Subjects of Emergency Handling of Newborn Resuscitation on Student Semester V NU At the University of Surabaya in 2015. in conclusion the learning model Jigsaw type of students more active, creative and better learning outcomes compared to conventional methods. With the use of appropriate learning models will be able to improve student results.